2020
DOI: 10.1101/2020.04.14.039800
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Leveraging Fungal Calcineurin-Inhibitor Structures, Biophysics and Dynamics to Design Selective and Non-Immunosuppressive FK506 Analogs

Abstract: Calcineurin is an attractive antifungal target due to its central role in fungal pathogenesis. The development of specific antifungals targeting calcineurin is complex, as calcineurin inhibitors, such as FK506, are immunosuppressive. Using fungal calcineurin-inhibitor crystal structures we recently developed a less immunosuppressive FK506 analog, APX879, with broad-spectrum antifungal activity and efficacy in a murine model of invasive fungal infection. To better understand the interaction of the human and fun… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 56 publications
(107 reference statements)
0
4
0
Order By: Relevance
“…The CnaA residue W377 is required for FK506-CnaA hydrophobic interaction and spontaneous mutation resulting in W377L was predicted to disrupt the hydrophobic pocket at the binding interface (Lee et al, 2015). Gobeil et al (2020) found that the amino acid sequence of McFKBP12 is 58% identical to HsFKBP12. The sequence variations were present in the 40, 50, and 80s extended loops surrounding the FK506 binding pocket.…”
Section: Mucor Circinelloidesmentioning
confidence: 99%
See 3 more Smart Citations
“…The CnaA residue W377 is required for FK506-CnaA hydrophobic interaction and spontaneous mutation resulting in W377L was predicted to disrupt the hydrophobic pocket at the binding interface (Lee et al, 2015). Gobeil et al (2020) found that the amino acid sequence of McFKBP12 is 58% identical to HsFKBP12. The sequence variations were present in the 40, 50, and 80s extended loops surrounding the FK506 binding pocket.…”
Section: Mucor Circinelloidesmentioning
confidence: 99%
“…The sequence variations were present in the 40, 50, and 80s extended loops surrounding the FK506 binding pocket. Interestingly, McFKBP12 sequence is 65% identical to AfFKBP12 and share structural similarity but functionally they are not equivalent in inhibiting calcineurin function (Gobeil et al, 2020). When Affkbp12 was replaced with Mcfkbp12 in A. fumigatus, FK506 was not able to inhibit calcineurin function.…”
Section: Mucor Circinelloidesmentioning
confidence: 99%
See 2 more Smart Citations